Analytical data for GB-Ob: Tenbury MS 389 and GB: McGhie (private collection) - Butler, K (University of Oxford, 2017)
Data created during the AHRC-funded Tudor Partbooks project 2014-17 following the opportunity to photograph and examine the McGhie partbook. The data underpins the article 'Creating a Tudor Musical Miscellany: The Tenbury/McGhie Partbooks' (forthcoming). Digital images of both the McGhie and Tenbury partbooks are available on DIAMM (www.diamm.ac.uk): <www.diamm.ac.uk/sources/2680/#/> and <www.diamm.ac.uk/sources/2325/#/>